2014
DOI: 10.2147/cpt.s44805
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythm and cardiovascular disorders

Abstract: Abstract:Circadian rhythmicity affects all living organisms on earth. Central and peripheral cellular clocks have the ability to oscillate and be entrained to environmental cues, thus allowing organisms to anticipate and synchronize their physiologic processes and behavior to recurring daily environmental alterations. Disruption of the circadian rhythm in modern life, such as by shift work and jet travel, leads to dyssynchrony of the central and peripheral clocks, and is an independent risk factor for cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 153 publications
(174 reference statements)
0
3
0
Order By: Relevance
“…The classic example of chronic circadian disruption is shift working. Early observations showed that shift workers have higher-than-average incidence of adverse cardiovascular events, including myocardial infarction, strokes, and sudden cardiac death (76)(77)(78)(79)(80)(81), with a predilection for events occurring in the early morning hours. While behavior changes associated with shift working (and not the disruption of circadian clock per se) may also have contributed, it is of particular interest that the exposure time to shift working showed a linear correlation with the load of cardiac diseases (82).…”
Section: R E V I E W S E R I E S : C I R C a D I A N R H Y T H Mmentioning
confidence: 99%
“…The classic example of chronic circadian disruption is shift working. Early observations showed that shift workers have higher-than-average incidence of adverse cardiovascular events, including myocardial infarction, strokes, and sudden cardiac death (76)(77)(78)(79)(80)(81), with a predilection for events occurring in the early morning hours. While behavior changes associated with shift working (and not the disruption of circadian clock per se) may also have contributed, it is of particular interest that the exposure time to shift working showed a linear correlation with the load of cardiac diseases (82).…”
Section: R E V I E W S E R I E S : C I R C a D I A N R H Y T H Mmentioning
confidence: 99%
“…CLOCK and ARNTL (BMAL1) heterodimers form a positive loop that stimulates PER and CRY transcription and other clock-linked genes. A negative feedback loop is composed of PER and CRY heterodimers, which inhibits the transcription of CLOCK and ARNTL genes [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular Effects: (David Salisbury, 2013;Jain, Zhang, & Sabeh, 2014) Each cell involved in the cardiovascular system have their own molecular clocks which should be coordinated with the central clock for synchronized response of the body to diurnal variations in their environment.…”
Section: Introductionmentioning
confidence: 99%